2017
DOI: 10.1056/nejmoa1615822
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Prophylaxis plus Antiretroviral Therapy for Advanced HIV Infection in Africa

Abstract: Background In sub-Saharan Africa, among patients with advanced human immunodeficiency virus (HIV) infection, the rate of death from infection (including tuberculosis and cryptococcus) shortly after the initiation of antiretroviral therapy (ART) is approximately 10%. Methods In this factorial open-label trial conducted in Uganda, Zimbabwe, Malawi, and Kenya, we enrolled HIV-infected adults and children 5 years of age or older who had not received previous ART and were starting ART with a CD4+ count of fewer t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
190
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 174 publications
(197 citation statements)
references
References 23 publications
6
190
0
1
Order By: Relevance
“…Health centers and clinics, for example, had proportions of advanced disease of 15% and 16%, respectively, in 2016 with historic proportions above 20% for certain years. Similar to the REALITY trial that showed significant proportions of patients with advanced disease at outpatient wards [8], our data suggests that primary care facilities have high proportions of patients with advanced HIV disease that also require the advanced HIV disease package of care in order to minimize HIV-related morbidity and mortality [6].…”
Section: Resultsmentioning
confidence: 65%
See 1 more Smart Citation
“…Health centers and clinics, for example, had proportions of advanced disease of 15% and 16%, respectively, in 2016 with historic proportions above 20% for certain years. Similar to the REALITY trial that showed significant proportions of patients with advanced disease at outpatient wards [8], our data suggests that primary care facilities have high proportions of patients with advanced HIV disease that also require the advanced HIV disease package of care in order to minimize HIV-related morbidity and mortality [6].…”
Section: Resultsmentioning
confidence: 65%
“…CD4 is recommended to monitor patients at risk for opportunistic infections and to identify patients with advanced HIV disease [3,6,7]. Though clinical acumen can be used to identify patients with advanced HIV disease-defined as patients with a CD4 <200 cells/mm 3 or WHO clinical stage 3 or 4 disease [6]-it has been found to be poorly accurate: up to 50% of patients with advanced disease may be asymptomatic (WHO clinical stage 1 or 2) and thus missed by clinical acumen alone [8].…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, access to baseline CD4 testing, screening and management of opportunistic (tuberculosis, cryptococcal meningitis) and access to prophylaxis (isoniazid preventive therapy & pre-emptive fluconazole) remains a challenge in the Zimbabwe’s public sector [50, 51]. Recent evidence has also shown that screening, prophylaxis and management of opportunistic diseases (mainly tuberculosis, bacterial sepsis and cryptococcal disease) significantly reduce morbidity and mortality [52, 53]. However, evidence from this enhanced care package is currently being poorly implemented by most ART programmes in low resource setting [54].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, prevention of TB through strengthening of TB diagnostic approaches and implementation of strong preventive strategies to children on ART has been suggested. Notably, newly emerging prophylaxis regimen in the prevention of TB [42] needs to be considered. More emphasis is required for the first 6 months after ART initiation.…”
Section: Discussionmentioning
confidence: 99%